DOES AN INTERVENTION TO REDUCE MATERNAL ANXIETY, DEPRESSION AND TRAUMA ALSO IMPROVE MOTHERS' PERCEPTIONS OF THEIR PRETERM INFANTS' VULNERABILITY?. Issue 1 (1st December 2014) - Horwitz, Sarah Mccue; Leibovitz, Ann; Lilo, Emily; Jo, Booil; Debattista, Anne; St. John, Nick; Shaw, Richard J.
ABSTRACT To determine if an intervention to reduce maternal distress and address maternal perceptions of infants' vulnerability also reduces perceptions of vulnerability, 105 mothers of premature infants (25‐ to 34‐weeks' gestational age; >600 g) with depression, anxiety, or trauma were randomized to a six‐ or nine‐session intervention or a comparison condition. The outcome was changes in a measure of perception of infant vulnerability between 4 to 5 weeks' and 6 months' postdelivery, the Vulnerability Baby Scale (VBS; B. Forsyth, S. Horwitz, J. Leventhal, & J. Burger, 1996; N. Kerruish, K. Settle, P. Campbell‐Stokes, & B. Taylor, 2005). High scores on the VBS were indicative of high levels of perceived infant vulnerability. The perceptions of infants' vulnerability showed significant declines, with no differences across groups or in rate of change. Mothers reporting prior trauma at entry to the study showed much lower perceptions of infants' vulnerability scores under the intervention, Cohen's d = −0.86, p = .01. Given that women with prior trauma are very likely to view their premature infants as vulnerable, this intervention may have important implications for subsequent parenting behaviors and child development.